Management of linear quadratic regulator optimal control with full-vehicle control case study. (26th September 2016) - Tchamna, Rodrigue; Lee, Moonyong; Youn, Iljoong; Maxim, Vladislav; Židek, Kamil; Kelemenová, Tatiana
Linear quadratic regulator is a powerful technique for dealing with the control design of any linear and nonlinear system after linearization of the system around an operating point. For small systems, which have fewer state variables, the transformation of the performance index from scalar to matrix form can be straightforward. On the other hand, as the system becomes large with many state variables and controllers, appropriate design and notations should be defined to make it easy to automatically implement the technique for any large system without the need to redesign from scratch every time one requires a new system. The main aim of this article was to deal with this issue. This article shows how to automatically obtain the matrix form of the performance index matrices from the scalar version of the performance index. Control of a full-vehicle in cornering was taken as a case study in this article.